First glaciological investigations at Ridge B, central East Antarctica. Issue 4 (August 2021) - Ekaykin, Alexey A.; Bolshunov, Alexey V.; Lipenkov, Vladimir Ya.; Scheinert, Mirko; Eberlein, Lutz; Brovkov, Evgeniy; Popov, Sergey V.; Turkeev, Alexey V.
Abstract: The region of Ridge B in central East Antarctica is one of the last unexplored parts of the continent and, at the same time, ranks among the most promising places to search for Earth's oldest ice. In January 2020, we carried out the first scientific traverse from Russia's Vostok Station to the topographical dome of Ridge B (Dome B, 3807 m above sea level, 79.02°S, 93.69°E). The glaciological programme included continuous snow-radar profiling and geodetic positioning along the traverse's route, installation of snow stakes, measurements of snow density, collection of samples for stable water isotope and chemical analyses and drilling of a 20 m firn core. The first results of the traverse show that the surface mass balance at Dome B (2.28 g cm −2 year −1 ) is among the lowest in Antarctica. The firn temperature below the layer of annual variations is −58.1 ± 0.2°C. A very low value of heavy water stable isotope content (-58.2‰ for oxygen-18) was discovered at a distance of 170 km from Vostok Station. This work is the first step towards a comprehensive reconnaissance study of the Ridge B area aimed at locating the best site for future deep drilling for the oldest Antarctic ice.